AKUMULASI KADMIUM (CD) PADA IKAN NILEM SEBAGAI BIOINDIKATOR PENCEMARAN LOGAM BERAT DI KALIGARANG - Rossi Prabowo; Purwanto Purwanto; Henna Rya Sunoko (Universitas Wahid Hasyim, 2012)
Industrial development along Garang Watershed has been worrying people for allegedly nearly all plants waste products into Garang watershed that would trigger changes in water quality, which can lead to contamination of the river water. Cadmium and Lead are toxic substances that cause chronic poisoning in human. Both types of heavy metals have very high toxicity value and much produced as industrial waste that is along Garang Watershed. This research is an exploratory observation with a quantitative approach that has purpose to describe the content of heavy metals Cd and Pb in water, sediment, wader fish (Puntius bramoides), nilem fish (Osteochilus hasselti), lunjar fish (Rasbora argyrotaenia) in Kaligarang. The result of this research suggests that the content of heavy metal Cd on Kaligarang average of 0008 mg/l and the content of heavy metal Pb average of 0020 mg/l. The content of heavy metals Cd and Pb in Kaligarang sediment vary. The content of heavy metal Cd between 0.0071 mg/kg - 0.0474 mg/kg, while the content of heavy metal Pb between 0.0493 mg/kg - 0.3481 mg/kg. The research of the content of Cd and Pb in wader fish (Puntius bramoides), nilem fish (Osteochilus hasselti), lunjar fish (Rasbora argyrotaenia) in Kaligarang suggests that the highest content of Cd and Pb is found in nilem fish (Osteochilus hasselti) liver, that is the content of Cd 0.096 mg/kg and Pb 0.180 mg/kg at station 3. This value is substandard set by the FDR New Zealand, FAO, and SNI. 7387.2009, About Heavy Metal Contamination Maximum Limit in Food. Accumulation of heavy metals Cd and Pb in fish between Tugu Suharto and Simongan station is relatively similar. It is caused the location both of stations adjacent to the condition of water are relatively slope slightly and quiet, making it easier for fish organism migrates between both of stations. Nilem Fish (Osteochilus hasselti) is the best bio indicator for heavy metals Cd and Pb because it can accumulate heavy metals Cd and Pb greater than wader fish (Puntius bramoides) and lunjar fish (Rasbora argyrotaenia). Kaligarang is a standard water source of drinking water, it should be intensified in Garang Watershed management, so it can reduce contamination into Kaligarang. Keywords: Accumulation, Cadmium (Cd), Lead (Pb), Bioindicator